Effects on Drivers' Behavior of Forward Collision Warning System Alerts. (September 2016) - Fisher, Donald L.; Nodine, Emily; Lam, Andy; Jerome, Christian; Monk, Chris; Najm, Wassim
Forward collision warning (FCW) systems have been available for some time. Drivers 20-29 years of age are especially at risk for being involved in motor vehicle crashes due to distraction. (FCW) systems could potentially reduce rear-end crashes caused by distraction and other factors. A field operational experiment was run to determine whether FCW systems could reduce over time for this cohort the driving conflicts (rear-end crashes and near crashes) with lead vehicles. Information was gathered on 38 drivers over varying periods of time (up to a year) on alert rates [over vehicle miles traveled (VMT) or months], conflict rates, and responses to conflicts. Conflicts per 1, 000 VMT decreased by 76.6%. The decrease in conflict rates was correlated with the decrease in alert rates (0.71), suggesting that drivers were responding positively to the alerts. There was no change in the responses to conflicts. Females had many fewer alerts than males.